PENGARUH PEMBELAJARAN BERBASIS PROYEK TERHADAP KETERAMPILAN REKAYASA LALU LINTAS PADA MATA KULIAH PEMINDAHAN TANAH MEKANIS & JALAN RAYA - Firdaus Caesar Albantani (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
In the course of Soil Mechanics & Road Engineering, students only receive instruction from teachers and do not have the opportunity to learn freely or systematically. Therefore, the education system should be more interactive and engaging to enable students to learn more freely and systematically. Teachers should have the ability to make the material more interesting and influential so that students can understand it better. The method used is Literature Review, which involves collecting and analyzing data from various sources of literature, such as articles, books, slides, and internet information, is known as a literature review process. Literature review is used in road engineering education to support students' knowledge and skills. In the subject of Soil Mechanics & Road Engineering, the application of project-based learning with a constructivist approach is an appropriate choice. This approach enhances learning performance and helps students achieve their learning goals. According to the project, learning increases students' ability to solve transportation problems in the field, enhances their teamwork skills, increases their enthusiasm, and makes them more independent and creative. The use of project-based learning (PBL) models in the Soil Mechanics & Road Engineering course can help students improve academic quality, skills, and understanding of building construction. Project-based learning with a constructivist approach can improve students' learning performance and achieve learning goals. The project-based learning model has a positive effect on learning, such as making it easier for students to understand the material during learning.